Critical Environmental Factors Affecting Social Entrepreneurship as a Tool for Sustainable Development in the Townships in KwaZulu-Natal Province - Akoh, Emmanuel Inalegwu; Lekhanya, Lawrence Mpele (Re-engineering Business Processes in the New Normal - The Business and Economic Development Post COVID-19 and the Restructuring of the Global Economy: Proceedings of 8th International Conference on Business and Management Dynamics, 2023)
Social entrepreneurship is prescribed in literature to play an important role in achieving sustainable development globally. However, social entrepreneurship faces many challenges that affect its effectiveness in solving social problems. A general lack of in-depth understanding is found by policy makers and other relevant stakeholders of the factors that could hinder social entrepreneurship as a tool for sustainable development in South Africa, especially in the townships in KwaZulu-Natal. This lack of understanding leads to the continuous failure of social entrepreneurship to thrive and grow, resulting in this study, with the aim to address this research gap, by investigating social entrepreneurs’ views on critical environmental factors affecting their contribution to sustainable development. A quantitative research approach was used to collect and analyse data for the study, with primary data collected from three townships in the KwaZulu-Natal province. Ninety social entrepreneurs participated in the study and the questionnaire was self-administered by the researcher to each respondent. It was found that the lack of adequate resources, poor policy and regulations, rapid technological changes, and corruption, as well as the COVID-19 impact, lack of management competence and skills, and lack of education and training development, along with a lack of marketing skills, were some of the critical environmental factors affecting social entrepreneurship in KwaZulu-Natal townships. It is recommended government establish laws and regulations pertinent to social enterprises, with the specific view to eliminate the confusion regarding what legislative framework governs them, while it is suggested financial institutions provide capacity training to nurture social enterprise business ideas, more so for those in the townships. Moreover, for social entrepreneurship to thrive, grow, and contribute to sustainable township development, government needs to develop a conducive environment.